ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN PROFOTABILITAS PADA KOPERASI SERIBU KUBAH KUBU BABUSSALAM ROKAN HILIR - Delvin Pidayani; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Cooperative is a business entity consisting of a single person or cooperative legal entity based on its activities based on cooperative principles as well as a people's economic movement based on the principle of kinship.The purpose of this study was to determine the condition of working capital in increasing profitability and the efficiency of working capital used to increase profitability in the Thousand Kubah Cooperative. This research was conducted at the Seribu Kubah Cooperative addressing Jend Sudirman, Rantau Panjang Left, Kubu - Kubu Babussalam Subdistrict during the period of 2014 to 2018. The analysis used was descriptive by looking at the ratio of ratio to the specified standard ratio. The liquidity ratio which consists of assets liquidity ratio in the category is very good with an average value of 258.85%. While the loan to total assets ratio is also in the good category with an average value of 50.02% and the loan to deposit ratio in the category is very good with an average value of 179.96%. While the value of profitability ratios consisting of return on assets in the category is not good with an average value of 49.87%. While return on equity in the good category with an average value of 69.1% and net profit margin in the category is very good with an average value generated at 71.17%. And the capital ratio consisting of equity total assets in the good category with an average value generated by 72.18% and equity to total loans in the category very good with an average value generated by 145.31%.Keywords:Liquidity,Profitability,andCapital